Growth Response of Antanan (Centella asiatica L.) to Dosage of Chicken Manure And Planting Media Composition - Yulianti, Nani; Goheri, Goheri; Rochmana, Nur (Universitas Djuanda, 2023)
Antanan (Centella asiatica L.) is a plant that has high nutritional content and active compounds that are beneficial for health. This research aims to determine the effect of doses of chicken manure and planting media on the growth and production of antanan. The research used a factorial completely randomized design (CRD). The first factor is the composition of the planting medium which consists of four levels, namely: M1 (100% soil = 980g), M2 (50% soil = 490g, 50% husk charcoal = 125g), M3 (75% soil = 735g, 25% husk charcoal = 62 g), M4, (25% soil = 245g, 75% husk charcoal = 187g). The second factor is the dose of chicken manure consisting of five levels, namely: P2 (100% chicken manure = 133g), P4 (75% chicken manure = 100g), P6 (50% chicken manure = 67g), P8 (25% chicken manure = 33g), P10 (15% chicken manure = 20g). The results of the research showed that the dose of chicken manure and the composition of the planting media had a significant effect on the growth and production of antanan plants. A dose of 100% chicken manure resulted in better growth in leaf area, number of leaves, dry weight and fresh weight of the crown, dry weight and fresh weight of plant stover, as well as root dry weight compared to other treatments. In the mixed planting media composition treatment of 75% soil + 25% husk charcoal, the value of the stolon length of antanan plants was better compared to other media compositions, while for the root length variable the best value was shown in the planting media composition of 25% soil + 75% husk charcoal.